Synthesis of NaYF4:Yb/Er/Gd up-conversion luminescent nanoparticles and luminescence resonance energy transfer-based protein detection - Zhang, Jingpu (2011)
High-quality NaYF(4):Yb/Er/Gd up-conversion nanoparticles (UCNPs) were first synthesized by a solvothermal method using rare earth stearate, sodium fluoride, ethanol, water, and oleic acid as precursors. Doped Gd(3+) ions can promote the transition of NaYF(4) from cubic to hexagonal phase, shorten the reaction time, and reduce the reaction temperature without reducing the luminescence intensity of NaYF(4):Yb/Er UCNPs. X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and luminescence spectroscopy were applied to characterize the UCNPs. The nanoparticles exhibited small size and excellent green up-conversion photoluminescence, making them suitable for biological applications. After the surfaces of NaYF(4):Yb/Er/Gd UCNPs were modified with amino groups through the Stöber method, they could be brought close enough to the analytically important protein called R-phycoerythrin (R-PE) bearing multiple carboxyl groups so that energy transfer could occur. A luminescence resonance energy transfer (LRET) system was developed using NaYF(4):Yb/Er/Gd UCNPs as an energy donor and R-PE as an energy acceptor. As a result, a detection limit of R-PE of 0.5 μg/ml was achieved by the LRET system with a relative standard deviation of 2.0%. Although this approach was first used successfully to detect R-PE, it can also be extended to the detection of other biological molecules.